2020
DOI: 10.1088/1361-6471/ab9b06
|View full text |Cite
|
Sign up to set email alerts
|

Quark matter at finite temperature under strong magnetic fields within Nambu–Jona-Lasinio model

Abstract: The quark matter symmetry free energy and the thermodynamical properties of strange quark matter (SQM) in strong magnetic fields and non-zero temperature cases are discussed in this work within Nambu–Jona-Lasinio (NJL) model by considering two kinds of vector interactions. The properties of the proto-quark stars (PQSs) are also studied by introducing a density-dependent magnetic field strength distribution and assuming two ‘extreme’ magnetic orientation cases inside the quark stars (QSs). The results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Some of the examples are: MIT bag model [36,37], Dyson-Schwinger equation approach [38][39][40][41], quark meson coupling (QMC) model [42], quark mass density dependent (QMDD) model [43][44][45][46][47], Nambu-Jona-Lasinio (NJL) model [37,48], confined density dependent quark mass (CDDM) model [8,49,50], chiral SU(3) quark mean field (CQMF) model [51,52], Polyakov quark meson coupling (PQMC) model [53,54] and Polyakov extended NJL (PNJL) model [55][56][57]. Many authors have studied the properties of pure SQM in β-equilibrium [58-61], proto-strange quark stars (PSQS) [62][63][64][65][66][67], as well as hybrid star with SQM in the core [68,69] (also, see references therein).…”
Section: (): V-volmentioning
confidence: 99%
“…Some of the examples are: MIT bag model [36,37], Dyson-Schwinger equation approach [38][39][40][41], quark meson coupling (QMC) model [42], quark mass density dependent (QMDD) model [43][44][45][46][47], Nambu-Jona-Lasinio (NJL) model [37,48], confined density dependent quark mass (CDDM) model [8,49,50], chiral SU(3) quark mean field (CQMF) model [51,52], Polyakov quark meson coupling (PQMC) model [53,54] and Polyakov extended NJL (PNJL) model [55][56][57]. Many authors have studied the properties of pure SQM in β-equilibrium [58-61], proto-strange quark stars (PSQS) [62][63][64][65][66][67], as well as hybrid star with SQM in the core [68,69] (also, see references therein).…”
Section: (): V-volmentioning
confidence: 99%
“…The possible existence of QSs is still one of the most important fields of modern nuclear physics and astrophysics [12][13][14][15][16][17][18][19][20][21][22][23][24]. If one considered the supermassive compact stars as QSs, the observations may rule out some of the conventional phenomenological models of quark matter, whereas there still exist some other models which are able to produce massive quark star cases with strong isospin interaction inside the star matter [25][26][27][28][29][30][31][32][33][34]. It can be found that the EOS of the quark star matter in their descriptions becomes very stiff so as to support such massive quark stars.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a strong magnetic field introduces Landau levels for the charged particles and hence has significant effects on the stability of SQM [30][31][32]. The properties of SQM in a strong magnetic field have attracted increasing interest over the past few decades, for example, the effects of an external magnetic field on the symmetry energy [33,34], equation of state [35] and surface tension of quark matter [36], and r-mode instability [37,38] as well as structure properties of strange stars [39][40][41][42][43], etc. In addition, the presence of a magnetic field can also affect the in-medium chiral condensates [44], and hence the critical temperature of the chiral phase transition [45][46][47][48][49][50][51][52], as well as the deconfinement transition [53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%